Diagnostic significance of microRNA-1255b-5p in prostate cancer patients and its effect on cancer cell function. Issue 2 (20th December 2021) - Zhao, Yuling; Tang, Xiaochun; Zhao, Yifan; Yu, Yan; Liu, Shuzhen
ABSTRACT: Discerning between indolent and aggressive types is a big challenge of prostate cancer clinically to guide the adequate therapeutic regimen. We aimed to examine the relationship between miR-1255b-p expression and prostate cancer and elucidate the function of miR-1255b-5p in prostate cancer. miR-1255b-5p were measured using Quantitative Real-Time PCR from the blood 103 benign prostate hyperplasia (BPH) and 153 prostate cancer patients (117 indolent cases and 36 upgrading cases). Using receiver operating characteristic (ROC) curve analysis, the discriminating ability of miR-1255b-5p was accessed between BPH and prostate cancer participants, or indolent and aggressive type. Using CCK-8 and Transwell assays, the function of miR-1255b-5p on prostate cancer cells was investigated. The levels of miR-1255b-5p were significantly raised in prostate cancer patients when compared with BPH participants. MiR-1255b-5p level can distinguish prostate cancer patients from BPH or indolent type from aggressive type. Downregulation of miR-1255b-5p can suppress the proliferative, invasive, and migratory capacity, but this effect can be eradicated by EPB41L1 inhibition. The measurement of miR-1255b-5p in blood may provide a new noninvasive approach for the diagnosis of prostate cancer. miR-1255b-5p may become a potential therapeutic target for prostate cancer.